Brief Report: Sound Output of Infant Humidifiers. (June 2015) - Royer, Allison K.; Wilson, Paul F.; Royer, Mark C.; Miyamoto, Richard T.
The sound pressure levels (SPLs) of common infant humidifiers were determined to identify the likely sound exposure to infants and young children. This primary investigative research study was completed at a tertiary-level academic medical center otolaryngology and audiology laboratory. Five commercially available humidifiers were obtained from brick-and-mortar infant supply stores. Sound levels were measured at 20-, 100-, and 150-cm distances at all available humidifier settings. Two of 5 (40%) humidifiers tested had SPL readings greater than the recommended hospital infant nursery levels (50 dB) at distances up to 100 cm. In this preliminary study, it was demonstrated that humidifiers marketed for infant nurseries may produce appreciably high decibel levels. Further characterization of the effect of humidifier design on SPLs and further elucidation of ambient sound levels associated with hearing risk are necessary before definitive conclusions and recommendations can be made.